2014
DOI: 10.1002/jmri.24729
|View full text |Cite
|
Sign up to set email alerts
|

Knee implant imaging at 3 Tesla using high‐bandwidth radiofrequency pulses

Abstract: The application of high-bandwidth RF pulses by local transmit coils substantially reduces through-plane distortion artifacts at 3 Tesla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
1
19
0
2
Order By: Relevance
“…MARS techniques work successfully at the knee despite the minor surrounding soft tissue and the more complex metal anatomy (Fig. ) . For unilateral knee replacements, a clinical relevance was shown for SEMAC STIR sequences .…”
Section: Clinical Applicationmentioning
confidence: 96%
See 1 more Smart Citation
“…MARS techniques work successfully at the knee despite the minor surrounding soft tissue and the more complex metal anatomy (Fig. ) . For unilateral knee replacements, a clinical relevance was shown for SEMAC STIR sequences .…”
Section: Clinical Applicationmentioning
confidence: 96%
“…These include possibly switching frequency and phase‐encoding direction, increasing the bandwidth of the receiver or transmit pulses, increasing the matrix size for in‐plane artifact reduction, and reducing the slice thickness for through‐plane artifact reduction . Using high‐bandwidth RF pulses has also been shown to substantially reduce through‐plane distortion artifacts, at the cost of an increased blurring . In contrast to previous assumptions, new studies have shown that longer echo trains do not reduce metal artifacts…”
Section: Hardware and Pulse Sequencesmentioning
confidence: 99%
“…Spulen lassen den Einsatz von Radiofrequenzpulsen mit sehr hoher Bandbreite (4 kHz) zu, was eine starke ebenenübergreifende Artefaktkorrektur mit Scan-Zeiten von 7-9 Minuten ermöglicht (▶Abb. 11) [11].…”
Section: Compressed Sensingunclassified
“…A T/R-knee coil with high signal-to-noise and multiple elements was used at a field strength of 3.0 T to allow for the implementation of these techniques. The T/R-coil allows for a higher B1 amplitude due to the reduced excited field of view and for a reduced overall SAR compared to conventional techniques that use the body coil for excitation [24,25]. The results are a higher signal-to-noise ratio, sharper pulse profiles and shorter pulse durations.…”
Section: Comparison To Arthroscopic Knee Surgerymentioning
confidence: 99%
“…The latter is difficult to fully account for in sagittally oriented 2 D slices and likely leads to partial volume effects that The significantly lower incidence of artifacts in 3D-PDwFS was mostly related to the decreased pulsation artifacts that are usually observed in 2D-PDwFS, especially in sagittal planes due to AP phase-encoding direction. These were not observed in sagittal MPR of 3D-PDwFS and may be attributed to the excitation pulse that covers a larger slab in 3D-PDwFS [5,7,24,26,27]. This has certain advantages in the case of preparation pulses, e. g. for fat suppression or inversion.…”
Section: D-pdwfs 2d-pdwfs P-valuementioning
confidence: 99%